Perjanalan menuju kebahagiaan: Studi fenomenologis pengalaman koping spiritual positif pada ibu tunggal perempuan kepala keluarga - Dewi, Kartika Sari (Jurnal Psikologi Ulayat, 2024)
The number of woman-headed households in Indonesia is increasing every year, and many of them experience a decreased in well-being due to factors such as intrapersonal conflict in family management, financial instability, increased parental burden as a single parent, and social prejudice. Spirituality could be one of their coping strategies. This study aims to reveal the experience of positive spiritual coping of woman-headed households in achieving their happiness. A snowball sampling technique was applied to recruit ten woman participants (30–48 years old) who had been heads of household for at least two years. This qualitative research used a phenomenological design with thematic analysis. The results of the study revealed that participants’ spiritual coping facilitated resilience and happiness attainment. Two main themes emerged from participants’ responses: positive spirituality coping and self-happiness that develops from adaptive mental processes. In contrast to previous studies, the results of this study elucidate positive spiritual coping as a pivotal factor in fostering mothers’ happiness. This is achieved through the cultivation of positive mindsets, attitudes, and emotions, even amids challenging living circumstances and the demands of independence.